The impact of N-acetylcysteine on hypoxia-induced testicular apoptosis in male rats: TUNEL and IHC findings - Majid Shokoohi; Amir Afshin Khaki; Leila Roshangar; Mohammad Hossein Nasr Esfahani; Gilda Ghazi Soltani; Alireza Alihemmati (Heliyon)
The present study aimed to evaluate the impact of N-acetylcysteine (NAC) on testicular hypoxia caused by varicocele, focusing specifically on the regulation of genes related to apoptosis and oxidative stress in the testes of mature Wistar rats.Thirty-two rats were divided into four groups: Control (Sham), hypoxia, testicular hypoxia treated with NAC (Hypoxia + NAC), and healthy animals treated with NAC. After the 8-week treatment period, testicular histopathology and the levels of oxidative stress markers—superoxide dismutase (SOD), glutathione peroxidase (GPx), and malondialdehyde (MDA)—in serum were examined. The expression of Bax and Bcl-2 mRNA was analyzed using immunocytochemistry and RT-qPCR assays, while the apoptosis rate was determined using the TUNEL method.Histopathological evaluations showed that parameters such as Johnsen's score, epithelium width, and seminiferous tubule diameter indicated significant improvement in the Hypoxia + NAC group compared to the Hypoxia group. NAC administration resulted in elevated serum levels of GPx and SOD, accompanied by a reduction in MDA levels (p < 0.003). Furthermore, the study revealed that NAC decreased Bax expression and enhanced Bcl-2 gene and protein expression compared to the varicocele group (p < 0.05). Additionally, NAC administration significantly decreased the rate of apoptosis in germ cells (p < 0.05).These findings suggest that NAC administration can mitigate testicular damage induced by hypoxia from varicocele in rats, primarily due to its antioxidant properties.